Upregulation of iNOS Protects Cyclic Mechanical Stretch-Induced Cell Death in Rat Aorta Smooth Muscle Cells - Zhao, Jing (Int J Mol Sci, 2020)
Aortic dissection and aneurysm are associated with abnormal hemodynamic loads originating from hypertension. Our previous study demonstrated that cyclic mechanical stretch (CMS, mimicked hypertension) caused the death of rat aortic smooth muscle cells (RASMCs) in a mitogen activated-protein kinases (MAPKs)-dependent manner. The current study investigated the effects of inducible nitric oxide synthase (iNOS) on CMS-induced RASMC death. cDNA microarrays for CMS-treated RASMCs showed that iNOS expression levels were increased in response to CMS. Real-time polymerase chain reaction (PCR) analysis demonstrated that this increase was p38 MAPK (p38)-dependent. NO production was also increased. This increase could be inhibited by p38 and iNOS inhibitors. Thus, CMS-induced iNOS synthesized NO. CMS-induced cell death in RASMCs was increased by the iNOS inhibitor but abrogated by the long-acting NO donor DETA-NONOate. Increased iNOS expression was confirmed in the abdominal aortic constriction mouse model. Signal transducers and activators of transcription 1 (STAT1) was activated in stretched RASMCs, and iNOS expression and NO production were inhibited by the STAT1 inhibitor nifuroxazide. Our findings suggest that RASMCs were protected by iNOS from CMS-stimulated cell death through the STAT1 and p38 signal pathways independently.